Non-invasive regional study of chronic cerebrovascular disorders using the oxygen-15 inhalation technique. Issue 1 (January 1978) - Lenzi, G L; Jones, T; McKenzie, C G; Moss, S
Abstract : The regional cerebral metabolism-to-perfusion imbalance has been studied in the three main categories of cerebrovascular disorders in a chronic phase of the disease, using the non-invasive oxygen-15 inhalation technique. In patients presenting with a history of transient ischaemic attacks, regional defects in cerebral perfusion were greater than for the corresponding oxygen uptakes. Areas of relative ischaemia within which there was an enforced increase in the oxygen extraction ratio were highlighted. The reverse pattern was observed frequently in patients with brain infarcts arising from strokes, so indicating areas of relative luxury perfusion as is inferred from the reduction in the oxygen extraction ratio. In the multi-infarct dementia group of patients, there were parallel focal reductions in both flow and metabolism. The oxygen-15 inhalation technique is shown to be a unique tool in investigating cerebrovascular disorders because of its non-invasiveness and its ability to define regional metabolism-to-perfusion imbalance within the brain.